Amanah Sharing and Protection–Knowledge as a Strategy in Securing Organizational Knowledge - Fadjar Setiyo Anggraeni (Faculty of Economics and Business, Universitas Wahid Hasyim, 2024)
This study aims to identify and explore the mechanism of knowledge protection in organizations, as well as develop the concept of Amanah Sharing and Protection-Knowledge as a strategy to maintain strategic knowledge. The methods used include literature studies and analysis of various previous studies that discuss knowledge protection in knowledge-intensive business service (KIBS) companies operating in different sectors. The results of the study indicate that there are various approaches to knowledge protection, including formal and strategic protection, as well as the importance of a secure attitude from human resources in maintaining the confidentiality of knowledge. This study also contributes to organizational leaders to recruit individuals who have a secure nature and build an organizational culture that supports a religious attitude, so that strategic knowledge can be integrated well and remain secure in the long term. In addition, the results of this study provide input for policy makers regarding public policies that can help companies protect their competitive knowledge capital without hindering the interactions needed for innovation.